2020
DOI: 10.3390/ani10091622
|View full text |Cite
|
Sign up to set email alerts
|

Farming Practices Influence Antibiotic Resistance and Biogenic Amine Capacity of Staphylococci from Bulk Tank Ewe’s Milk

Abstract: Staphylococci are one of the main microorganisms responsible for intramammary infections in sheep, causing important economic losses for farmers and eventually health problems in humans, especially by the consumption of dairy products made with raw milk containing toxic compounds, such as biogenic amines or antibiotic resistant bacteria. This study aimed to check the presence and safety of staphylococci in bulk tank ewe’s milk from different farms, and to determine the relationship between the presence of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The difference among Staphylococcus isolates in terms of amino acid decarboxylase activity is in accordance with previous studies (Anderegg et al, 2020;Sang et al, 2020) which reported that the production of biogenic amines could vary significantly at the isolate level. Our data confirmed that the production of biogenic amine is an isolated specific trait as reported earlier (Jeong et al, 2014;Poveda et al, 2020). A wide range of data has been reported on the production of biogenic amines by staphylococcal isolates.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The difference among Staphylococcus isolates in terms of amino acid decarboxylase activity is in accordance with previous studies (Anderegg et al, 2020;Sang et al, 2020) which reported that the production of biogenic amines could vary significantly at the isolate level. Our data confirmed that the production of biogenic amine is an isolated specific trait as reported earlier (Jeong et al, 2014;Poveda et al, 2020). A wide range of data has been reported on the production of biogenic amines by staphylococcal isolates.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is necessary to monitor the biogenic amines in raw and processed milk due to their toxicity and usefulness as milk spoilage index. Bacterial decreasing methods for milk, such as high pressure, irradiation, pasteurization, or homogenization, diminish the levels of biogenic amine producing bacteria; however, there is evidence concerning contamination and production of biogenic amines in raw and processed milks (Gavina Manca et al, 2020;Poveda et al, 2020;Pivetta et al, 2020;Mousavi Khaneghah et al, 2020). In this study, in light of previous data supporting probiotics advantages, we examined the effects of L. lactis and B. bifidum (two probiotic bacteria) on the HDC and TDC genes of Staphylococcus species isolated from raw milk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, IMIs have been identified as important causes of (i) welfare concerns in ewes [ 4 ]; and (ii) public skepticism regarding the safety and quality of milk and the products thereof [ 2 ]. The zoonotic potential of specific pathogens, antibacterial resistance due to the extensive use of antibiotics for the treatment of IMIs, and antibiotic residues in milk and meat, have emerged as public health hazards [ 5 , 6 ]. Nowadays, the existed legal and regulatory framework has not substantially described a comprehensive mitigation strategy against IMIs at the farm level in dairy ewes; instead, the extrapolation of data from dairy cattle is the norm, since studies to assess possible risk factors in dairy sheep are scarce.…”
Section: Introductionmentioning
confidence: 99%